Wastewater treatment : (CRC Press, 2013)
The book explores recent advances in wastewater treatment by various technologies such as chemical methods, biochemical methods, membrane separation techniques, and by application of Fenton and solar photo Fenton methods. It emphasizes new technologies that produce clean water and energy from the wastewater treatment process and addresses sustainable water reclamation, biomembrane treatment processes and advanced oxidation processes for wastewater treatment.